Influence of temperature on swine maternity: bibliographic review (Research, Society and Development, 2020)
The correct management of the farm in all stages of creation brings positive results, since, the incorrect practice brings negative results resulting in losses in production. The fact that the majority of swine females live in the intensive system (small space cages) has been a topic that has been widely discussed when it comes to animal welfare. Pigs reared in the confined system, have no physical or psychological privacy, lacking space to move freely and are isolated socially involved by a monotonous production system. The animal needs to be in a thermal comfort zone where it feels good with its external environment, otherwise, it will go into thermal discomfort, leading to hypothermia (cold stress) or hyperthermia (heat stress), such changes cause damage without return, and can lead the animal to death. The objective of this review is to address stress in the swine maternity, exposing improvements in what concerns animal welfare, since stress causes physiological changes that leads to an imbalance of homeostasis, causing problems with no return to animals, such as reducing zootechnical performance and / or reproductive problems, even death.